Prevalence and Determinants of Gestational Diabetes Mellitus in a Tertiary Care Hospital: A Cross-Sectional Analysis - Hemasa Gul, Huma Gul, Fatima Rehman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Gestational Diabetes Mellitus (GDM) is one of the most common metabolic disorders during pregnancy and is associated with adverse maternal and fetal outcomes. Early identification of risk factors is essential for timely intervention. This study aimed to determine the prevalence of GDM and identify associated risk factors among pregnant women attending a tertiary care hospital. Study Design: A Cross-Sectional study. Place and Duration of the Study: The study was conducted at the Department of Obstetrics and Gynecology at Mardan Medical Complex, Mardan from January 2023 to June 2023. Materials &Methods: A hospital-based cross-sectional study was conducted among 178 pregnant women between 24–36 weeks of gestation. Participants were selected using consecutive sampling. Data were collected using a structured questionnaire covering sociodemographic, obstetric, and clinical characteristics. GDM was diagnosed using standard oral glucose tolerance test (OGTT) criteria. Data were analyzed using SPSS version 26.0. Logistic regression analysis was performed to identify independent predictors of GDM. Adjusted odds ratios (AOR) with 95% confidence intervals (CI) were calculated, and p < 0.05 was considered statistically significant. Results: The prevalence of GDM was 15.7% (28/178). Higher maternal age (≥35 years) was significantly associated with GDM (AOR = 3.12; 95% CI: 1.08–9.02; p = 0.035). Obesity (AOR = 3.76; 95% CI: 1.41–10.01; p = 0.008), family history of diabetes (AOR = 3.24; 95% CI: 1.32–7.94; p = 0.010), previous history of GDM (AOR = 5.87; 95% CI: 1.78–19.36; p = 0.004), and chronic hypertension (AOR = 2.69; 95% CI: 1.01–7.18; p = 0.048) were independent predictors of GDM. Overweight status and grand multiparity were not statistically significant in the adjusted model. Conclusion: The prevalence of GDM in this tertiary care setting was moderately high (15.7%). Advanced maternal age, obesity, family history of diabetes, previous GDM, and chronic hypertension were significant risk factors. Routine screening and targeted interventions for high-risk women are recommended to reduce adverse pregnancy outcomes. Keywords: Gestational diabetes mellitus, prevalence, risk factors, pregnancy, obesity, tertiary care hospital, cross-sectional study.